2012
DOI: 10.1159/000336352
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Gastroesophageal Junction Adenocarcinoma and <i>Helicobacter pylori</i> Infection in Japan

Abstract: Background/Aims: The relationship between gastroesophageal junction adenocarcinoma (GEJA) and Helicobacter pylori infection is not well defined; thus, we retrospectively investigated this relationship. Methods: We examined 852 cases (646 men) of gastric cancer. GEJA was defined as type II according to the classification system of Siewert and Stein. We compared the prevalence of H. pylori infection and corporal gastritis in GEJA patients with distal gastric cancer. Results: GEJA was observed in 80 (including 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…While early studies claim that H. pylori infection is only related to distal or ‘non-cardia' gastric cancer, this is no longer true since there is clear evidence now for the pathogenetic relevance also in proximal gastric cancer or adenocarcinomas at the esophagogastric junction, if proper allocation of the tumor and assessment of the relevant risk factor are performed [15,16,17]. The risk for gastric carcinogenesis by H. pylori infection is similar for intestinal- and diffuse-type gastric cancers [15,18].…”
Section: Helicobacter Pylori - Epidemiological Backgroundmentioning
confidence: 99%
“…While early studies claim that H. pylori infection is only related to distal or ‘non-cardia' gastric cancer, this is no longer true since there is clear evidence now for the pathogenetic relevance also in proximal gastric cancer or adenocarcinomas at the esophagogastric junction, if proper allocation of the tumor and assessment of the relevant risk factor are performed [15,16,17]. The risk for gastric carcinogenesis by H. pylori infection is similar for intestinal- and diffuse-type gastric cancers [15,18].…”
Section: Helicobacter Pylori - Epidemiological Backgroundmentioning
confidence: 99%
“…Some miRNAs have been shown to possess oncogenic or tumour suppressor activity and relate to apoptosis, proliferation, differentiation, metastasis, angiogenesis and immune response, which are all potentially involved in cancer initiation, progression and treatment response (Lu et al , 2005; Wang et al , 2010). There have been an increasing number of studies showing overexpression or downregulation of specific miRNAs in various malignant tumours including gastric cancer and H. pylori -infected gastric mucosa (Okubo et al , 2010; Hishida et al , 2011; Kamada et al , 2012; Shiotani et al , 2012a). …”
mentioning
confidence: 99%
“…69 Meanwhile, Derakhshan et al suggested that cardia cancer had two distinct etiologies: one arising from chronic gastritis similar to non-cardia cancer, and the other related to GERD similar to esophageal adenocarcinoma 21 and this was confirmed later in a study by Horii et al 22 In Western countries, most EGJ adenocarcinomas have characteristics similar to those of esophageal adenocarcinomas, in contrast to Asian countries where most have characteristics similar to those of distal gastric cancers. 22,70 The reason for the above difference between the West and East may be the more frequent incidence of H. pylori-related gastric cancers and ethnicity factors in the East. The variable prevalence of GERD, obesity, and H. pylori infection, and the pattern of gastric atrophy (corpus-or antrum-predominant) may explain the observed differences in incidence and time trends between the three Asian countries.…”
Section: Surgical Treatmentmentioning
confidence: 99%